Social Network Analysis of Mangrove Ecosystem Management: Understanding Stakeholder Interaction in Mundu, Cirebon - Feti Fatimatuzzahroh; Liza Indina (Universitas Negeri Semarang, 2025)
Effective management of mangrove ecosystems is essential for the conservation of these vital habitats and the maintenance of their ecosystem services. This process involves multiple stakeholders to ensure sustainability. This study aims to identify the stakeholders involved in mangrove management in Mundu, Cirebon, map their relationships, and assess their roles within this context. Employing a qualitative approach, the research describes stakeholder involvement in mangrove ecosystem management and utilizes UCINET 6 software for analysis. This analysis identifies the stakeholders with the strongest engagement and those playing pivotal roles in mangrove management. The findings indicate that the primary actors in mangrove management in Mundu are the Community-Based Coastal Resource Management group (Pokmaswas), which has a degree centrality of 1.2222; the Village Government, with a value of 1.3333; and the Department of Marine Affairs and Fisheries, which has a value of 0.6666. These results suggest that both Pokmaswas and Village Governments play central roles in mangrove management, with the Department of Marine Affairs and Fisheries following closely behind. This highlights the critical contribution of community groups to the success of mangrove conservation efforts in the region. However, UCINET analysis also reveals that interactions among stakeholders are limited, indicating a gap in collaboration. This lack of interaction may lead to suboptimal management and hinder the development of the mangrove ecosystem in Mundu.